Invasive hemodynamic parameters in patients with hepatorenal syndrome. (October 2022) - Pelayo, Jerald; Lo, Kevin Bryan; Sultan, Sahar; Quintero, Eduardo; Peterson, Eric; Salacupa, Grace; Zanoria, Martin Angelo; Guarin, Geneva; Helfman, Beth; Sanon, Julien; Mathew, Roy; Yazdanyar, Ali; et al.
Abstract: Background: Hepatorenal syndrome (HRS), a form of kidney dysfunction frequent in cirrhotic patients, is characterized by low filling pressures and impaired kidney perfusion due to peripheral vasodilation and reduced effective circulatory volume. Cardiorenal syndrome (CRS), driven by renal venous hypertension and elevated filling pressures, is a separate cause of kidney dysfunction in cirrhotic patients. The two entities, however, have similar clinical phenotypes. To date, limited invasive hemodynamic data are available to help distinguish the primary forces behind worsened kidney function in cirrhotic patients. Objective: Our aim was to analyze invasive hemodynamic profiles and kidney outcomes in patients with cirrhosis who met criteria for HRS. Methods: We conducted a single center retrospective study among cirrhotic patients with worsening kidney function admitted for liver transplant evaluation between 2010 and 2020. All met accepted criteria for HRS and underwent concurrent right heart catheterization (RHC). Results: 127 subjects were included. 79 had right atrial pressure >10 mmHg, 79 had wedge pressure >15 mmHg, and 68 had both. All patients with elevated wedge pressure were switched from volume loading to diuretics resulting in significant reductions between admission and post diuresis creatinine values (2.0 [IQR 1.5–2.8] vs 1.5 [IQR 1.2–2.2]; p = 0.003). Conclusion: 62% of patients diagnosed with HRS by clinical criteria have elevated filling pressures. Improvement of renal function after diuresis suggests the presence of CRS physiology in these patients. Invasive hemodynamic data profiling can lead to meaningful change in management of cirrhotic patients with worsened kidney function, guiding appropriate therapies based on filling pressures.